2018
DOI: 10.1097/scs.0000000000004095
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngoscopic Analyses through Anterior Maxillary Distraction Osteogenesis for Adolescent Patients With Cleft Palate

Abstract: Anterior maxillary distraction osteogenesis (AMDO) is a novel technique for correcting hypoplastic maxilla by sagittal expansion of the maxilla. Recent reports suggest that AMDO does not have an effect on fragile velopharyngeal function in patients with cleft palate. Furthermore, no studies have evaluated the impact of AMDO on velopharyngeal function. We adopted AMDO to correct severe hypoplastic maxilla in adolescent patients with cleft palate and evaluated its impact on velopharyngeal space and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
3
1
0
1
Order By: Relevance
“…[29][30][31] Some studies have also reported improvement in speech parameters and velopharyngeal closure following AMD. 9,28,32 Our findings are in accordance with these studies. This serves as one of the greatest merits of the procedure.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…[29][30][31] Some studies have also reported improvement in speech parameters and velopharyngeal closure following AMD. 9,28,32 Our findings are in accordance with these studies. This serves as one of the greatest merits of the procedure.…”
Section: Discussionsupporting
confidence: 93%
“…No signs of velopharyngeal morphologic changes or speech deterioration was noted even in patients with pre-existing VPI in the previous studies 29–31 . Some studies have also reported improvement in speech parameters and velopharyngeal closure following AMD 9,28,32 . Our findings are in accordance with these studies.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Para funcionar como terapia REM la expansión se prescribe un cuarto de vuelta (0.25 mm), dos veces por día (5). Se realiza hasta que las cúspides palatinas de los primeros molares superiores entren en contacto con las cúspides bucales de los primeros molares inferiores (1,3,(5)(6)(7)(8). Hasta obtener en promedio 5 +-1 mm de expansión transversal en un lapso de 5.5+-1.0 meses (3,4,8).…”
Section: Introductionunclassified